Identification of Chemical Compounds of Guava Leaf Fractions using Phytochemical Test, UV-Vis Spectrophotometry and GC-MS - Wardani, Lailatul Munawaroh Dewi Kusuma; Andayani, Sri; Maimunah, Yunita (JST (Jurnal Sains dan Teknologi), 2025)
Fraction is the result of fractionation of the process of separating compounds based on the polarity properties of the solvent. Thin layer chromatography is the first step in fractionation analysis to determine the eluent that can produce guava leaf fractions. The guava leaf fraction contains chemical compounds that play a role in improving the immune system. Guava leaves contain flavonoid compounds, especially quercetin. The effort made to find out the content of guava leaves is to analyze further. Some analyses to determine the content of active compounds, especially in guava leaf fractions, are using phytochemical tests, UV-VIS spectrophotometry, and GC-MS. The combination of these three methods can obtain comprehensive information about the content of chemical compounds in plants, from the identification of compound groups to the characteristics of specific compounds. Phytochemical analysis is an initial analytical method carried out to examine the content of chemical compounds in medicinal plants. Ultra Violet-Visble (UV-Vis) spectrophotometer is one of the chemical analysis methods to determine the composition of a sample, both quantitatively and qualitatively, based on the interaction between matter and light. The Gas Cromatography-Mass Spectrometry (GC-MS) method is a method of separating samples using gas chromatography while analyzing the compounds using mass spectroscopy. The purpose of this study is to analyze the active compounds contained in the guava leaf fraction. This research uses a qualitative method by collecting data by observation and literature study.  The results showed that the results of the analysis of guava leaf fractions using phytochemical tests, UV-VIS spectrophotometers, and GC-MS, showed that the fraction contained terpenoid and flavonoid group compounds.